The Use of Infliximab for Treatment of Hospitalized Patients with Acute Severe Ulcerative Colitis. (2008) - Bressler, B; Law, JK; Al Nahdi Sheraisher, N; Atkinson, K; Byrne, MF; Chung, HV; Fishman, M; Partovi, N; Pearson, D; Penner, R; Enns, RA
Abstract : BACKGROUND/AIM: The use of infliximab in severe ulcerative colitis (UC) is established; however, its role in severe acute UC requires clarification. The present multicentre case series evaluated infliximab in hospitalized patients with steroid-refractory severe UC. METHODS: Patients from six hospitals were retrospectively evaluated. Data collection included demographics, duration of disease and previous treatments. The primary end point was response to in-hospital infliximab; defined as discharge without colectomy. RESULTS: Twenty-one patients (median age 26 years) were admitted between May 2006 and May 2008 with severe UC requiring intravenous steroids and given infliximab (median time to infusion eight days). Sixteen (76%) patients were discharged home without colectomy; three of these underwent colectomy at a later date. Of the remaining 13 patients (62%), all but two did not require further courses of steroids; six patients had infliximab as a bridge to azathioprine and seven patients were maintained on regular infliximab. Five patients required in-hospital colectomy after the initial infliximab. CONCLUSIONS: In this real-life experience of infliximab in patients with steroid-refractory severe UC, infliximab appears to be a viable rescue therapy. The majority of patients were discharged without surgery and 62% maintained response either as a bridge to azathioprine or maintenance infliximab.